Peran Sikap dan Kemampuan Mengingat Iklan Online Terhadap Keputusan Pembelian Traveloka - Melia Astiana (Universitas Pendidikan Nasional, 2021)
This study aims to analyze the influence of attitude towards online advertising and ability to recall online advertising on Traveloka purchasing decisions. In an effort to attract online consumers to make a decision to purchase a product or service offered by the company, online advertising is often used by many companies to create awareness of the organization and its products and services. Data obtained from 105 respondents using a questionnaire. This study uses multiple linear regression as a data analysis technique. From the regression equation obtained, the independent variable that has the most significant value is attitude towards online advertising. Hypothesis testing using t test shows that attitude variable towards online advertisement and the ability to recall online advertisement, both variables significantly influence purchasing decision. While in f test showed significant <0,05. This means that attitude towards online advertising (x1) and the ability to recall online advertising (x2) together have a significant effect on purchasing decisions (y). While the coefficient of determination obtained by value adjusted R2 41.6%. It means that the purchasing decision variable can be explained by the attitude towards online advertising and the ability to recall online advertising, while the remaining 58.4% can be influenced by other variables.